Effect of magnesium sulfate on cerebral vasospasm in the treatment of aneurysmal subarachnoid hemorrhage: a systematic review and meta-analysis - Zheng, Hanlin; Guo, Xiumei; Huang, Xinyue; Xiong, Yu; Gao, Wen; Ke, Chuhan; Chen, Chunhui; Pan, Zhigang; Ye, Lichao; Wang, Lingxing; Hu, Weipeng; Zheng, Feng (Frontiers in Neurology, 2023)
Introduction The use of magnesium sulfate for treating aneurysmal subarachnoid hemorrhage (aSAH) has shown inconsistent results across studies. To assess the impact of magnesium sulfate on outcomes after aSAH, we conducted a systematic review and meta-analysis of relevant randomized controlled trials. Methods PubMed, Embase, and the Cochrane Library were searched for relevant literature on magnesium sulfate for aSAH from database inception to March 20, 2023. The primary outcome was cerebral vasospasm (CV), and secondary outcomes included delayed cerebral ischemia (DCI), secondary cerebral infarction, rebleeding, neurological dysfunction, and mortality. Results Of the 558 identified studies, 16 comprising 3,503 patients were eligible and included in the analysis. Compared with control groups (saline or standard treatment), significant differences were reported in outcomes of CV [odds ratio (OR) = 0.61, p = 0.04, 95% confidence interval (CI) (0.37–0.99)], DCI [OR = 0.57, p = 0.01, 95% CI (0.37–0.88)], secondary cerebral infarction [OR = 0.49, p = 0.01, 95% CI (0.27–0.87)] and neurological dysfunction [OR = 0.55, p = 0.04, 95% CI (0.32–0.96)] after magnesium sulfate administration, with no significant differences detected in mortality [OR = 0.92, p = 0.47, 95% CI (0.73–1.15)] and rebleeding [OR = 0.68, p = 0.55, 95% CI (0.19–2.40)] between the two groups. Conclusion The superiority of magnesium sulfate over standard treatments for CV, DCI, secondary cerebral infarction, and neurological dysfunction in patients with aSAH was demonstrated. Further randomized trials are warranted to validate these findings with increased sample sizes.